Thomas Reid : o problema da indução - Pimentel, Pablo Fernando Campos (2015)
The purpose of this paper is to present a possible reidian theory for a justification to the problem of induction from its two major writings, namely, "An Inquiry into the Human Mind on the Principles of Common Sense" 1764 and "Essays on the Intellectual Powers of Men" of 1785. Thus, appear quite subtle conception of Thomas Reid about "Problem of Induction", which is primarily discussed in the Inquiry, however, they appear quite important approaches and crucial also in Essays. It should not be forgotten that while the reidiana theory of induction is emerging, a debate and an analysis will be made by Reid in his great contemporary Hume. The importance of Hume's inclusion is indisputable because it has been Reid's time, and also by the contours of his thought about inductive reasoning and how Reid understands and, in a way, goes further. Therefore, some chapters will work with the problem of induction in the two respective works of Reid, HMI and EIP. It will also be an analysis of what was written about the induction and other peripheral issues in Reid, the other researchers. What conclusions Reid comes in and another work, and realize what critics synthesized his thinking in this respect, namely with regard to induction.